COMPARAÇÃO DO PERFIL EPIDEMIOLÓGICO DE TRANSTORNO DE DÉFICIT DE ATENÇÃO E HIPERATIVIDADE NAS REDES MUNICIPAL E PRIVADA DE ANÁPOLIS-GO - Ana Luiza Boni; Adriana Karla de Oliveira; Deon Vinícius Moreira Pimentel; Erick Nunes Melo; Isabela Louise Caldeira Silva; Lilian da Silva Aguiar; Mariana Paes de Oliveira; Víctor Henrique Araújo de Morais; Karla Cristina Naves de Carvalho (UniEVANGÉLICA, 2017)
Objective: To analyze the epidemiological profile and prevalence of signs and symptoms of Attention Deficit Disorder and Hyperactivity in children and adolescents of municipal and private schools in the city of Anápolis - GO. Methods: A cross-sectional study, comparative, descriptive study with quantitative approach. Regarding the profile, the criteria evaluated were gender, age, school year and responsible for the student. The parameters, epidemiology profile and prevalence of signs and symptoms of ADHD in children from private schools were compared to the only study already developed in the municipal school network, which involved the same theoretical methodology of achievement, entitled "Prevalence of Signals And Symptoms of Attention Deficit and Hyperactivity in Children and Adolescents of Anápolis - Goiás "The collected data were analyzed employing the Statistic Package for Social Sciences 16.0 for Windows (SPSS 16.0). Results: A total of 383 (50,6%) children and adolescents from private and 374 (49,4%) public network were analyzed. There was a higher prevalence of ADHD in males both in private schools (63.6%) and the public (83.3%) schools. The prevalence of ADHD in private schools in Anápolis is 5.74% (n = 22), while in municipal schools the figure was 6.42% (n = 24). Conclusion: The estimated prevalence of signs and symptoms of ADHD in the infant and juvenile population of Anápolis was 6.07%, being similar to those described in the literature, in different parts of the world